Restoring growth in Puerto Rico : overview and policy options - Collins, Susan Margaret; Bosworth, Barry, 1942-; Soto-Class, Miguel A. (Brookings Institution Press ; Center for the New Economy, 2006)
As a territory of the United States, Puerto Rico enjoys the benefits of key U.S. legal, monetary, security, and tariff systems, and its residents are U.S. citizens. In the decades following World War II, Puerto Rico emerged as one of the worlds fastest-growing economies. From 1950 to 1970 per capita income nearly doubled as a percentage of the U.S. average, making the island the richest economy in Latin America. Since the mid-1970s, however, labor force attachment has declined, economic growth has slowed, and the islands living standards have fallen further behind those on the mainland. Today more than half of all Puerto Rican children live below the U.S. poverty level. Why did Puerto Ricos economic progress stall? And more important, what can be done to restore growth? A number of overlapping concerns-- labor supply and demand, entrepreneurship, the fiscal situation, financial markets, and trade-- are at the heart of its economic difficulties. This is a companion volume to "Restoring Growth: The Economy of Puerto Rico" (Brookings, 2006), in which economists from Puerto Rico and the United States examine the islands economy and propose strategies for sustainable growth. This monograph summarizes the analyses published in that volume and presents a set of policy recommendations to increase employment, improve education, upgrade infrastructure, and fix government finances. Contributors include James Alm (Georgia State University), Barry P. Bosworth and Gary Burtless (Brookings Institution), Susan M. Collins (Brookings Institution and Georgetown University), Steven J. Davis (University of Chicago), Mara E. Enchautegui, Juan Lara, Luis A. Rivera- Batiz, and Orlando Sotomayor(University of Puerto Rico), Richard B. Freeman and Robert Z. Lawrence (Harvard University), Helen F. Ladd (Duke University), Rita Maldonado-Bear and Ingo Walter (New York University), Francisco L. Rivera-Batiz (Columbia University), and Miguel A. Soto-Class (Center for the New Economy)